Replication data for characterization of Phaseolus coccineus interspecific germplasm accessions for disease resistance, grain market class and yield attributes - Mukankusi, Clare; Amongi, Winnyfred; Sebuliba, Sulaiman; Musoke, Stephen; Acam, Catherine; Naluwooza, Claire (2021)
P. coccineus interspecific lines (Agronomic quality, resistance levels in Fusarium and Pythium root rot, seed attributes) (2012-07-10)